Predictors of mortality among under-five children in rural Ethiopia: a cross sectional study - Gebru Gebremeskel Gebrerufael; Bsrat Tesfay Hagos (BMC, 2023)
Abstract Background Under-five child mortality (UFCM) is one of the major significant and sensitive indicators of the health status of the public. Although the world has seen a remarkable and substantial decrease in UFCM since 1990, its progression rate still remains alarmingly high in Sub-Saharan African (SSA) countries, particularly in Ethiopia. Therefore, this study aimed to assess associations between mortality and under-five children in rural Ethiopia. Methods This study used a secondary data analysis of the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS) report. A total of 4,425 under-five children were included in the final analysis. The Kaplan-Meier (K-M) and Cox proportional hazard (PH) model analyses were utilized to estimate survival time and investigate the major predictors of mortality in under-five children, respectively. An adjusted hazard ratio (AHR) along with a 95% confidence interval (CI) was employed to measure the association size and direction of the association (STATA 12). Results The study showed that 6.2% (95% CI: 5.43, 6.86) of children died beforehand celebrating their fifth birthday in rural Ethiopia. The multivariable Cox PH regression model analysis revealed associations of large spacing preceding birth interval (16-26 months) (AHR = 0.61; 95% CI: (0.402-0.920)), 27-38 months (AHR = 0.72; 95% CI: (0.496-1.03)), and ≥ 39 months, multiple births (AHR = 3.9; 95% CI: (2.77-5.62)), being breastfeeding (AHR = 0.13; 95% CI: (0.099-0.162)), and unvaccinated child (AHR = 11.6; 95% CI: (1.62-83.1)) were significant associations of under-five children mortality. Conclusions In this study, the UFCM rate was present, with 6.2% in the rural areas of Ethiopia. The birth type, preceding birth interval, vaccination of the child, and breastfeeding are identified as significant associations with under-five child mortality in rural Ethiopia. Therefore, public health interventions should be given attention to multiple births, unvaccinated, and non-breastfeeding children, as well as mothers' better encouragement to have a large spacing preceding the birth interval. Moreover, investigators should conduct continuous research on UFCM, which is imperative to provide current information and inform interventions in a timely manner.